CAR-T Cells for the Treatment of Lung Cancer - Luisa Chocarro; Hugo Arasanz; Leticia Fernández-Rubio; Ester Blanco; Miriam Echaide; Ana Bocanegra; Lucía Teijeira; Maider Garnica; Idoia Morilla; Maite Martínez-Aguillo; Sergio Piñeiro-Hermida; Pablo Ramos; et al. (Life, 2022)
Adoptive cell therapy with genetically modified T lymphocytes that express chimeric antigen receptors (CAR-T) is one of the most promising advanced therapies for the treatment of cancer, with unprecedented outcomes in hematological malignancies. However, the efficacy of CAR-T cells in solid tumors is still very unsatisfactory, because of the strong immunosuppressive tumor microenvironment that hinders immune responses. The development of next-generation personalized CAR-T cells against solid tumors is a clinical necessity. The identification of therapeutic targets for new CAR-T therapies to increase the efficacy, survival, persistence, and safety in solid tumors remains a critical frontier in cancer immunotherapy. Here, we summarize basic, translational, and clinical results of CAR-T cell immunotherapies in lung cancer, from their molecular engineering and mechanistic studies to preclinical and clinical development.